3D printing technique applied in vaginoplasty: A case report. Issue 12 (December 2022) - Yin, Guo-wu; Han, Tao; Liang, Jia-he; Yi, Jiang-pu; Wang, Jing-jing; Gao, Zhao-wei; Ren, Jing-chun; Fu, Qian; Li, Yun; Jin, Ling-li; Fei, Rong; Cao, Tie-sheng; et al.
Abstract: Background: We present the first case report of the treatment of congenital vaginal atresia by 3D-printed patient-specific vaginal scaffold from China. Case presentation: A 17-year-old female patient was referred to our department for treatment of congenital vaginal atresia and complications arising from previous failed operations. Pelvic examination was conducted to understand the morphological characteristics and severity of stenosis, and based on which we designed our prototypes of vaginal scaffold using software UG NX10.0. We finally obtained our patient-specific mold, which was 50 mm in length, 28 mm in diameter, 2 mm of thickness with a whole weight of 7.6 g, and it was made of polycaprolactone. After removing scar tissues caused by vaginal stenosis, an 8 cm long artificial tunnel was created, and then the polycaprolactone (PCL) vaginal mold was placed and sutured. The patient had no discomfort after surgery and was discharged 3 days after the surgery. Follow-up for 1 year after surgery, through hysteroscopy and colposcopy, it was found that the cervix was smooth, the vaginal wall was covered with stratified squamous epithelium, and the vaginal wall was soft and lubricated, which was close to a normal vagina. The incompletely absorbed mold was taken out one year after the operation. Hysteroscopy and colposcopy were performed one year and two years after the mold was taken out. The vagina was unobstructed and the length was about 12 cm. The appearance of the vaginal wrinkles was normal. The patient's quality of sexual life was good. Conclusion: Our team tried to treat congenital vaginal atresia by 3D-printed patient-specific vaginal scaffold, which can effectively reduce patient complications and reduce patient pain. Through long-term follow-up, we found that this technique has achieved favorable results and improved the patient's quality of sexual life. Abstract : Vaginoplasty; 3D printing; Vaginal mold; polycaprolactone.